2021
DOI: 10.3947/ic.2021.0090
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility to Biocides among Enterococci from Clinical and Non-Clinical Sources

Abstract: Background Wide use of biocidal agents such as benzalkonium chloride (BCC) and chlorhexidine digluconate (CHX) in hospitals and non-hospital environments, has raised concerns over the emergence of non-susceptible strains. Efflux pumps are of known main mechanisms in biocide tolerance which have been rarely addressed in enterococci - members of gut microbiota which can cause serious problems particularly in hospitalized patients. The purpose of this study was to investigate the susceptibility of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Despite the increased use of QACs in recent years ( 4 , 5 ), E. faecalis and E. faecium from various epidemiological backgrounds remain susceptible to QACs concentrations lower than those recommended for disinfection or preservation, with MIC and MBC distributions for BC and DDAC being consistent with previous reports ( 10 , 20 , 22 , 27 , 43 ). The observed similar QACs phenotypes in isolates with and without qacZ gene, along with supporting published data ( 20 , 22 ), suggest that QACs tolerance genes may not have a significant impact on the survival of Enterococcus spp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the increased use of QACs in recent years ( 4 , 5 ), E. faecalis and E. faecium from various epidemiological backgrounds remain susceptible to QACs concentrations lower than those recommended for disinfection or preservation, with MIC and MBC distributions for BC and DDAC being consistent with previous reports ( 10 , 20 , 22 , 27 , 43 ). The observed similar QACs phenotypes in isolates with and without qacZ gene, along with supporting published data ( 20 , 22 ), suggest that QACs tolerance genes may not have a significant impact on the survival of Enterococcus spp.…”
Section: Discussionsupporting
confidence: 87%
“…The apparent lack of selective advantage conferred by QACs tolerance genes in Enterococcus seems to be also corroborated by their low prevalence among Enterococcus isolates, which could be explained by rare horizontal transfer events, lack of stability of the acquired genes or genetic contexts due to, for example, high fitness costs ( 11 ). Accordingly, literature mostly supports that Enterococcus from diverse sources do not seem to be relevant reservoirs of known QACs tolerance genes ( 20 22 , 43 ), with few exceptions ( 24 , 25 ). In addition, we found that pre-exposure to BC did not induce a higher tolerance to this biocide in isolates carrying qacZ , which may indicate that the BC concentration and exposure times tested were not able to induce the gene expression of the efflux pump encoded by qacZ , that increased expression levels of qacZ did not lead to a detectable increase in Enterococcus tolerance to BC, or that other gene expression regulatory systems or environmental inductors are needed.…”
Section: Discussionmentioning
confidence: 99%
“…One of the 15 full-text examined papers had a sample size of fewer than 10 isolates and also, two studies were performed just on non-clinical isolates so, did not meet our inclusion criterion. Finally, 12 papers met the inclusion criteria and were submitted to our evaluation (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). A owchart of the literature search, the selection procedures and reasons for exclusion are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other authors have found significant differences across their Enterococcus spp. collections (Schwaiger et al, 2014;Duarte et al, 2019;Sobhanipoor et al, 2021;Kheljan et al, 2022;Pereira et al, 2022Pereira et al, , 2023. Most found a higher occurrence of strains with decreased susceptibility to CHX, DDAC, or BC among clinical isolates comparing to Enterococcus from other origins included in the same study (Schwaiger et al, 2014;Guzman Prieto et al, 2017;Duarte et al, 2019;Sobhanipoor et al, 2021;Pereira et al, 2023), although contradictory data has also been reported for BC (Sobhanipoor et al, 2021;Kheljan et al, 2022).…”
Section: Biguanidesmentioning
confidence: 99%